The energy transferred between lower-body segments by successful and less successful male rugby place kickers - Atack, A. C.; Trewartha, G.; Bezodis, N. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to understand how energy is transferred during a rugby place kick and how it differs between successful and less successful kickers. Senior male kickers (n=33) performed maximal range place kicks which were analysed using 3D motion capture (240 Hz), enabling segment powers to be determined. Energy was transferred out of the support leg throughout the backswing and early downswing, adding to the energy at the pelvis, which was subsequently transferred out as the kick knee extended towards the ball. Kickers who were limited by range, transferred less energy out of the support leg and into their kick foot, likely leading to a reduced kick foot and therefore, ball velocity. Appropriate support leg action appears important for achieving greater range in rugby place kicking.